2008
DOI: 10.1542/peds.2007-3770
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis After First Febrile Urinary Tract Infection in Children? A Multicenter, Randomized, Controlled, Noninferiority Trial

Abstract: For children with or without primary nonsevere reflux, prophylaxis does not reduce the rate of recurrent febrile urinary tract infections after the first episode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
190
0
24

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 316 publications
(215 citation statements)
references
References 18 publications
1
190
0
24
Order By: Relevance
“…These results are similar to those reported in other recent studies that evaluated the role of antimicrobial prophylaxis in reducing the risk of renal scarring (25)(26)(27)(28)(29). However, these results should not be interpreted as conclusive evidence against the role of antimicrobial prophylaxis in preventing renal scarring.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These results are similar to those reported in other recent studies that evaluated the role of antimicrobial prophylaxis in reducing the risk of renal scarring (25)(26)(27)(28)(29). However, these results should not be interpreted as conclusive evidence against the role of antimicrobial prophylaxis in preventing renal scarring.…”
Section: Discussionsupporting
confidence: 86%
“…The proportion of children with any renal scars in the RIVUR trial (10%) was higher than the 6% reported by Garin et al (25) and lower than the 30%-63% reported in other recent studies (26)(27)(28)(29). We believe that the low incidence of renal scarring in our study may be related to the exclusion of children with more than two febrile or symptomatic UTIs, careful monitoring for UTI recurrence, prompt intervention during the study period, generally younger study cohort, and the exclusion of children with grade 5 VUR in comparison to the study by Craig et al (28).…”
Section: Discussionmentioning
confidence: 52%
“…The efficacy of prophylactic antibiotics in preventing UTIs and further renal scarring has been tested in a number of recent studies [8][9][10][11][12] which were summarised in a metaanalysis in American guidelines [1]. This meta-analyse could not show any benefit from antibiotic prophylaxis over placebo treatment-irrespective of grade of VUR.…”
Section: Reasons For Changesmentioning
confidence: 99%
“…This is true for studies such as those on inflammatory markers and the rate of vesicoureteric reflux. Six studies have recently been published on antimicrobial prophylaxis for the prevention of recurrent UTI in infants and children with vesicoureteric reflux [19][20][21][22][23][24]. Three of these studies used mainly suprapubic aspiration or bladder catherisation [19][20][21], while the others relied on bag collection of urine [22][23][24].…”
Section: Consequences Of the Difficult Diagnosis Of Febrile Utimentioning
confidence: 99%